The Impact of Knowledge, Perception on the Major Amputation in People with Diabetic Foot Ulcers - Anum Arif; Nayab Munir Malik; Ahsin Manzoor Bhatti; Aima Sohail; Bismah Riaz; Mohammad Salman Imtiaz (Pakistan Armed Forces Medical Journal, 2023)
Objective: to evaluate the knowledge and practice of diabetic patients in terms of the diabetic foot and correlate it with the severity of diabetic foot and limb loss.